Stroke territory and atherosclerosis in ischemic stroke patients with a history of migraine with aura - Altamura, Claudia; Viticchi, Giovanna; Rizzo, Angelo Cascio; Maggio, Paola; Brunelli, Nicoletta; Marcosano, Marilena; Lazzaro, Vincenzo Di; Fiacco, Fabrizio; Agostoni, Elio Clemente; Silvestrini, Mauro; Vernieri, Fabrizio (Frontiers in Neurology, 2023)
The mechanisms subtending the increased stroke risk in migraine with aura (MA) are not fully understood. Our study aims to evaluate if the clinical profile in stroke patients with MA differentiates from those without MA. We retrieved the prospective registered electronic clinical dossiers of adult patients younger than 60 years with acute ischemic stroke admitted in four hospitals between January 2016 and June 2022. Patients were classified by the history of MA (MA+ and MA-). We identified 851 stroke patients (59 MA+, 6.9%). Compared to MA-, MA+ patients were characterized by younger age (44.0±10.6 vs 50.1±8.2 years), female sex (59.3% vs 29.0%), and affected by cryptogenic (OR 2.594 95%CI 1.483-4.537), and cerebellar stroke (OR 3.218 95%CI 1.657-6.250; p=<0.001 for all comparisons). After adjusting for age and sex, MA+ patients presented less frequently hypertension (OR 0.349 95%CI 0.167-0.470; p=0.005) and dyslipidemia (OR 0.523 95%CI 0.280-0.974; p=0.041). After adjusting also for risk factors, the MA+ group had less frequently symptomatic large vessel stenosis (OR 0.126 95%CI 0.017-0,924; p=0.042) and clinical atherosclerosis (OR 0.103 95%CI 0.014-0.761; p=0.026), while intima-media thickness did not differ (p=0.395). Cryptogenic and cerebellar stroke and fewer vascular risk factors and clinical atherosclerosis seem to characterize stroke patients with MA